Fabrication and in vitro Evaluation of 4-HIA Encapsulated PLGA Nanoparticles on PC12 Cells - Ravikiran T (Dove Medical Press, 2021)
Tekupalli Ravikiran,1 Santosh Anand,2 Mohammad Azam Ansari,3 Mohammad N Alomary,4 Sami AlYahya,4 Sowbhagya Ramachandregowda,1 Saad Alghamdi,5 Anupama Sindhghatta Kariyappa,1 Bhagyalakshmi Dundaiah,1 Mamatha Madhugiri Gopinath,1 Sumreen Sultana,1 Shital Manohar Punekar,1 Thimappa Ramachandrappa Lakshmeesha1 1Department of Biotechnology, Bangalore University, Bangalore, India; 2Department of Biotechnology, School of Applied Sciences, Reva University, Bengaluru, India; 3Department of Epidemic Disease Research, Institutes for Research and Medical Consultations (IRMC), Imam Abdulrahman Bin Faisal University, Dammam, 31441, Saudi Arabia; 4National Center for Biotechnology, Life Science and Environmental Research Institute, King Abdulaziz City for Science and Technology, Riyadh, Saudi Arabia; 5Laboratory Medicine Department, Faculty of Applied Medical Sciences, Umm Al-Qura University, Makkah, Saudi ArabiaCorrespondence: Thimappa Ramachandrappa LakshmeeshaDepartment of Biotechnology, Bangalore University, Bangalore, 560056, Karnataka, IndiaTel +91 8710937464Email lakshmeeshat6@gmail.comMohammad Azam AnsariDepartment of Epidemic Disease Research, Institutes for Research and Medical Consultations (IRMC), Imam Abdulrahman Bin Faisal University, Dammam, 31441, Saudi ArabiaTel +966 580306835Email maansari@iau.edu.saPurpose: 4-Hydroxyisophthalic acid (4-HIA) is a bioactive compound present in the roots of Decalepis hamiltonii, which has attracted considerable attention in attenuating oxidative stress-related neurodegenerative diseases. However, its efficacy is limited because of its low solubility and bioavailability. Therefore, the present study aimed to encapsulate 4-HIA using biocompatible copolymer polylactide-co-glycolide (PLGA) and evaluate its antioxidant and neuroprotective potential.Methods: The nanoparticles (NPs) were fabricated by solid/oil/water (s/o/w) emulsion technique and characterized using XRD, SEM, HR-TEM, and FTIR spectroscopy. Antioxidant assays such as 1,1 diphenyl-2-picrylhydrazyl (DPPH), superoxide, and hydroxyl radical scavenging ability were performed to assess the antioxidant potential of the fabricated NPs.Results: The bioactive component, 4-HIA, was efficiently encapsulated by the PLGA polymer and was found to be spherical and smooth with a size < 10nm. 4-HIA showed better scavenging capability in DPPH and superoxide assays as compared to 4-HIA encapsulated PLGA and butylated hydroxytoluene (BHT). In contrast, 4-HIA encapsulated PLGA NPs exhibited a significant hydroxyl radical scavenging activity than 4-HIA and BHT alone. Further, the encapsulated NPs efficiently curtailed hydrogen peroxide (H2O2)-induced cytotoxicity in PC12 cells.Conclusion: Our findings indicate that 4-HIA encapsulated PLGA NPs might be a therapeutic intervention towards the effective management of oxidative stress as it has exhibited efficient neuroprotective potential against H2O2-induced oxidative stress in PC12 cells.Keywords: 4-Hydroxyisophthalic acid, polylactic-co-glycolic acid, nanoencapsulation, PC12 cells, cytotoxicity